ESTIMATION OF CARBON RESERVED IN MANGROVE ECOSYSTEM OF ANAK SETATAH RANGSANG BARAT MERANTI ARCHIPELAGO DISTRICT RIAU PROVINCE - Hanif, Naufal; Siregar, Sofyan Husein; Amin, Bintal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThe research was conducted in January 2018 on mangrove ecosystem in coastal area of Anak Setatah Rangsang Barat Meranti archipelago district Riau Province. The purpose of this study was to estimated carbon reserved (mangrove carbon and soil organic carbon) in mangrove ecosystem on certain unit area. The method used in this research is survey method and analysis using allometric equation method to calculate how big biomass and mangrove carbon reserved in mangrove ecosystem. The results of this study that average mangrove carbon and soil organic carbon produced from each station per hectare was 583,32 ton/ha and 1546,81 ton/ha and CO2 absorption was 2138,85 ton/ha.Keyword : Mangrove, Carbon, Anak Setatah